PRAGMATICS TEST ASSESSMENT INNOVATION BASED HOTS IN ARABIC TEXTBOOKS CLASS XII - Khoirul Mubin; R. Umi Baroroh; Ahmad Suhendra Hasibuan; Ahmad Asron Mundofi; Mohammad Fadhlil Wafi (JURNAL TARBIYAH, 2025)
The Arabic textbook test for class XII published by the Ministry of Religious Affairs uses a pragmatic approach, but there are still questions that are at the MOTS level and less diverse in the variety of assessment forms, so it is not optimal in developing students' critical thinking skills. This study aims to analyse and develop innovative pragmatic approach tests in class XII Arabic textbooks published by the Ministry of Religious Affairs that are HOTS. This research is a library research. The results of this study show that some pragmatic tests in class XII Arabic textbooks have adopted the HOTS approach, especially in test types such as dictation, writing, storytelling, and interviews. However, it was also found that some tests were still at the MOTS level. This research provides innovations in HOTS-based pragmatics test instruments that are more varied, including dictation, translation, paraphrasing, cloze, and question and answer tests with detailed explanations of their cognitive implementation to improve Arabic language assessment.